The utilisation of public-private partnership: Fiscal responsibility and options to develop intervention strategies for HIV/AIDS in South Africa - Fourie, D.J. (David Johannes) (University of Pretoria, 2013)
Thesis (PhD (Public Affairs))--University of Pretoria, 2007.